Counter accounts of profit: outrage to action through "just" calculation. Issue 4 (11th July 2019) - Himick, Darlene; Ruff, Kate
Abstract : Purpose: Profit is often moralized by activists, but scant research has carefully examined what profit is for these activists or how they use it to create a more just world. The purpose of this paper is to investigate how social movements use counter accounts of profit as tools of resistance. Design/methodology/approach: A multiple case study design, informed by framing theory, is used to trace the framing of profit from activists' counter accounts to actions they precipitated. Specifically, the study examines counter accounts of profit from the UK abolition movement, Médecines Sans Frontières access to essential medicines campaign and Brigitte Bardot Foundation's opposition to the Canadian seal hunt, and how their framings of profit influenced change. Findings: Activists reframe profit to create visibilities and bridges to the suffering of distant others. Reframing the calculation and boundary of profit is a strategy to elicit moral outrage, hope and ultimately a more just world. Through these reframings, activists in three different social movements were able to change the possibilities of who and what can be profitable, and how. Social implications: The inherently incomplete nature of accounting frames give rise to accounting's vulnerability to non-accountants to assert their views of a moral profit. Accounting therefore is both a means of control at a distance but also "emancipation at a distance." Originality/value: Scholars have asserted that accounting can be used for resistance, few studies have examined how. By examining how activists assert what profit is – and should be – the paper documents and theorizes profit as contested and highlights accounting's emancipatory potential.